Management Model to increase inventory rotation in SMEs in the Mining Industry - Campos Espejo, Zenia Beatriz (2023)
Logistics is an area that determines, in many cases, the prosperity of a company. Regardless of its size, the search for new tools, procedures and management techniques has increased in recent years. In the mining sector, the 49,9% of companies do not have an inventory control mechanism; therefore, a low turnover of this. This can be for three reasons: inefficient purchasing policy, inadequate demand planning, and inadequate storage method. For this reason, a model conformed by the following tools was developed: ABC classification, JIT, MRP, and inventory management. Likewise, the Arena Software was used in an SMEs that imported drill bits for the mining industry to validate the described model. The results were a 62% improvement over the purchasing policy, a 73% decrease in cycle time, and only the use of one worker for theimport process, allowing the other worker to be in another area. Finally, with this research is possible to conclude that correct inventory management has a positive impact on the company's economy.